Synergistic action of essential oil of Ageratum conyzoides, Cymbopogon citratus, Eucalyptus globulus, and synthetic insecticides against the mosquito vector, Aedes albopictus Skuse (Diptera: Culicidae) - Dipsikha Bora; Jyoti Agrahari; Anisha Phukan; Beauti Kakoti; Sushila Chhetry; Kaushik Puzari; Inu Saikia; Shweta Bardhan; Himadri Borah (Journal of Basic and Applied Zoology)
Abstract Background Aedes albopictus is an epidemiologically important vector for the transmission of viral pathogens of yellow fever, dengue fever, chikungunya, zika, and filariasis. Plant-based products can provide environmentally safe mosquito control agents. Therefore, the efficacy of essential oils (EOs) extracted from Eucalyptus globulus, Ageratum conyzoides, and Cymbopogon citratus was determined against the larvae of A. albopictus. Results The highest larvicidal action was illustrated by the EO of E. globulus with an LC50 value of 46.58 ppm, followed by A. conyzoides with LC50 of 69.51 ppm. The efficacy of combinations of the EOs of the three plants at different ratios showed the combination of A. conyzoides with C. citratus at a 1:1 ratio to be the most effective with LC50 value of 13.05 with a 95% confidence limit of 10.54–15.32. The composition of the EOs analyzed using GC–MS showed precocene II and β-caryophyllene as major compounds of EO of A. conyzoides. We further evaluated the efficacy of the combination of EO with a binary combination of synthetic insecticides and detected the highest efficacy in a combination of A. conyzoides with malathion–cypermethrin and malathion–temephos. Conclusion Therefore, the EO of A. conyzoides, through synergistic action with organophosphate and pyrethroid synthetic insecticides, can effectively act against the vector of dengue, zika, and chikungunya. The EO of A. conyzoides or its major compounds can be explored for the development of mosquitocidal formulation using effective synthetic insecticides.